Variability in Soil Moisture by Natural and Artificial Snow: A Case Study in Mt. Balwang Area, Gangwon-do, South Korea - Nyamgerel, Yalalt; Jung, Hyejung; Koh, Dong-Chan; Ko, Kyung-Seok; Lee, Jeonghoon (Frontiers in Earth Science, 2022)
Soil moisture is an important variable for understanding various hydrological processes, particularly for water movement, solute transport, infiltration, and groundwater recharge. We have monitored the soil moisture and soil temperature in high (two sites) and low (two sites) elevation sites near to Mt. Balwang area in Gangwon-do, South Korea from Sep 2020 to May 2021. This study aims to investigate the temporal and spatial variations in soil moisture and soil temperature under influences due to spring snowmelt caused by natural and artificial snow. A ski resort has been operated in this area which have been creating an artificial snow during winter periods, thus the spring snowmelt consists of both natural and artificial snow. The results represent the presence of insulating snow layers (both natural and artificial), soil freezing, and wind conditions in the monitoring sites. We identified that the timing and intensity of snow cover and its spring snowmelt were distinct in each site. The high elevation sites show the increasing soil moisture by both precipitation (rain) and snowmelt, while the snowmelt signal was insignificant in the low elevation sites. The surface water, snowpit (artificial and natural), groundwater samples show a distinct stable water isotopic composition. Moreover, the ion concentration increased in the order of surface water > artificial snow > groundwater > natural snow. With the decreasing amount of natural snow in this region, the results support the assumption that the potential influence of artificial snowmelt on groundwater quality. This study will further help to understand the snow dynamic and its influence on the hydrological processes by combining the hydro-chemical and isotopic analysis.